THERMAL INSULATION EFFECTS ON ENERGY EFFICIENCY OF BUILDING STRUCTURES - M. Cvetkovska; M. Knezevic; M. Rogac (Journal of the Civil Engineering Forum, 2012)
This paper presents the use of Finite Element Method for heat transfer analysis. Connections wall-beam-floor structures with different positions of the thermal insulation have been analyzed and conclusions about energy efficiency and energy loss are made. Keywords: heat transfer, numerical analysis, finite elements, thermal insulation, energy efficiency.